2016
DOI: 10.1515/jpem-2016-0077
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress parameters in children with moderate iodine deficiency

Abstract: We found that children with moderate ID were exposed to more oxidative burden than children with mild ID or iodine sufficiency. Increased systemic oxidative stress induced by moderate ID could cause development of ID-related complications and diseases. Iodine supplementation could have a beneficial role in the prevention of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Firstly, since patients with thyroid nodular goiter often have concurrent thyroid antibodies, iodine deficiency thus may indirectly increase the TAI prevalence by increasing the prevalence of thyroid nodular goiter and causing damages to thyroid tissues (17,66,67,68,69). In addition, several studies have found that iodine can contribute to redox balance and iodine deficiency increases the degree of oxidative stress which may further promote immune response and increase autoimmune attack (70,71,72). Finally, TSH level is intensively related to iodine status, and iodine deficiency can result in increased TSH level (17,73).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, since patients with thyroid nodular goiter often have concurrent thyroid antibodies, iodine deficiency thus may indirectly increase the TAI prevalence by increasing the prevalence of thyroid nodular goiter and causing damages to thyroid tissues (17,66,67,68,69). In addition, several studies have found that iodine can contribute to redox balance and iodine deficiency increases the degree of oxidative stress which may further promote immune response and increase autoimmune attack (70,71,72). Finally, TSH level is intensively related to iodine status, and iodine deficiency can result in increased TSH level (17,73).…”
Section: Discussionmentioning
confidence: 99%
“…Iodine’s role in the growth and development of infants and children was also acknowledged [ 11 ]. Children with biochemical evidence of iodine deficiency experience a higher level of oxidative stress than their healthy peers with iodine sufficiency [ 19 ]. Conversely, iodine in excess is much less harmful as it may only affect a small percentage of sensitive individuals, whereas iodine deficiency can affect an entire cohort or parts of a population with endemic consequences [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients supplemented with iodine, the superoxidase level was decreased and antioxidant enzymes such as plasma catalase and glutathione peroxidase were increased, while erythrocyte glutathione peroxidase and the malonyl dialdehyde level indicating lipid peroxidation remained unchanged [29]. In a study which reported OS parameters to be higher in pediatric patients with moderate iodine deficiency (20–49 μg/L) than in patients with mild iodine deficiency (50–99 μg/L) or normal levels, TSH and thyroid autoantibodies were not analyzed [30]. In our study there was no difference between the OS parameters of patients with and without iodine deficiency.…”
Section: Discussionmentioning
confidence: 99%